Makeover welfare: Mary, Queen of Charity Shops and the cultural politics of second-hand under austerity. Issue 17 (9th December 2022) - Payson, Alida
Abstract : This paper brings together literature on welfare, austerity and second-hand cultures with theories of the makeover to analyse the cultural politics of charity shops in the UK, and their real aftereffects. Based on an analysis of two television programmes, a 2009 BBC Two reality television makeover programme Mary, Queen of Charity Shops, and a camp, cult-hit comedy web series, Charity Shop Sue (2019), the article traces the politics of makeover culture in second-hand spaces. In the first programme, retail celebrity Mary Portas sweeps in to make over a shabby British charity shop, sweeping out old things, people, and spaces, to make way for new ones. Tracing how the programme not only valorises but causes changes across the charity retail sector, the article shows how a regime of the makeover of things, people, and places in charity shops relates to a regime of real-world austerity politics I call makeover welfare, in which makeover is offered instead of welfare. Yet despite efforts to enforce makeover welfare, second-hand things, people, and places resist and escape this regime. In the second programme, analysing the camp satire of Charity Shop Sue's failed makeovers, I unpack second-hand's counter-aesthetic: a surprisingly durable second-hand politics located in unruly tatt, stubborn subjects, and rummage spaces. Further, because charity shops are important but overlooked instruments of welfare provision and governance, understanding their cultural politics opens up insights into how late capitalism is lived and felt.